Evaluation of practice change in Tanzanian health professionals 12 months after participation in an Infection Prevention and Management Course - Jones, Mark; Gower, Shelley; Whitfield, A.; Thomas, S. (Sage Publications, 2015)
Background: Hospital-acquired infection (HAI) is a problem confronting developing countries. Education programmes have been shown to be effective in increasing awareness and changing practice in health professionals. Methods: Practice change in health professionals who completed an Infection Prevention and Management Course in Tanzania was explored via focus group 12 months after completion of the course. Findings: Positive changes in infection control practice were found, along with barriers to more widespread change. Conclusions: Providing tailored and continuing education programs to hospital staff, including managers, is recommended.